The system of exercises for development of logical culture оn foreign language lessons (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article describes a set of exercises in forming of the speech competence, gives the system of exercises. When implemented sequentially in a class, the exercises will help develop logical culture on the lessons of foreign language.
Keywords: logical culture; exercises on development of the logical thinking and logical speech; analytical exercises